2006
DOI: 10.1021/pr0600024
|View full text |Cite
|
Sign up to set email alerts
|

Different Immunoaffinity Fractionation Strategies to Characterize the Human Plasma Proteome

Abstract: Plasma proteins may often serve as indicators of disease and are a rich source for biomarker discovery. However, the intrinsic large dynamic range of plasma proteins makes the analysis very challenging because a large number of low abundance proteins are often masked by a few high abundance proteins. The use of prefractionation methods, such as depletion of higher abundance proteins before protein profiling, can assist in the discovery and detection of less abundant proteins that may ultimately prove to be inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
142
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(143 citation statements)
references
References 45 publications
1
142
0
Order By: Relevance
“…The balance between dynamic range (quantitation of signal over orders of magnitude in target concentration) and sensitivity (both in terms of limit of detection, as well as signal disparity distinguishing comparable concentrations) is often difficult to maintain, as many proteins exist in low copy number (Anderson and Anderson, 2002), or the concentration span between basal and upregulated levels is large (Laack et al, 2002;Le et al, 2005). This difficulty is enhanced when attempting to selectively detect the target molecule in a complex solution (Yocum et al, 2005;Gong et al, 2006). A salient example of this challenge is the detection and quantitation of serum biomarkers of various ailments: for example, cytokines and chemokines (markers of infection and/or inflammation) can have concentration ranges between single pg/mL to hundreds of ng/mL, depending on their role in a specific response pathway (Fenton et al, 1997;Barrios-Rodiles et al, 1999;Ichiyama et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The balance between dynamic range (quantitation of signal over orders of magnitude in target concentration) and sensitivity (both in terms of limit of detection, as well as signal disparity distinguishing comparable concentrations) is often difficult to maintain, as many proteins exist in low copy number (Anderson and Anderson, 2002), or the concentration span between basal and upregulated levels is large (Laack et al, 2002;Le et al, 2005). This difficulty is enhanced when attempting to selectively detect the target molecule in a complex solution (Yocum et al, 2005;Gong et al, 2006). A salient example of this challenge is the detection and quantitation of serum biomarkers of various ailments: for example, cytokines and chemokines (markers of infection and/or inflammation) can have concentration ranges between single pg/mL to hundreds of ng/mL, depending on their role in a specific response pathway (Fenton et al, 1997;Barrios-Rodiles et al, 1999;Ichiyama et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Both 2DE and MALDI-MS analyses of the human serum proteins bound by both columns revealed no non-target proteins. However, previous serum depletion studies have reported the removal of non-target proteins [9][10][11]. This study demonstrates that, with some alteration to the given protocol, suitably depleted serum can be produced by IgY Spin Columns in the context of a biomarker study.…”
mentioning
confidence: 82%
“…Additionally, the concentration of a blood protein can range from less than 1-5 pg/ml to more than 55 billion pg/ml, stretching across seven logs (Zhang, Faca, and Hanash 2011). Immunodepletion columns have been developed to remove the top 6, 7, 12, 14, or 20 proteins from plasma/serum, prior to proteome profiling (Smith et al 2011;Gong et al 2006;Tu et al 2010). However, this procedure may also deplete potential proteins of interest that are bound to albumin in the blood stream, as well as low abundance proteins due to non-specific binding (Gong et al 2006).…”
Section: Choice Of Sample Typementioning
confidence: 99%